Fragmentation of CF4q+ (q=2,3) induced by 1-keV electron collisions - Chen, Lei; Wang, Enliang; Shan, Xu; Shen, Zhenjie; Zhao, Xi; Chen, Xiangjun (My University, 2021)
We report on an investigation on the fragmentation dynamics of CF4q+ (q=2,3) induced by 1-keV electron collisions utilizing an ion momentum imaging spectrometer. From the time-of-flight correlation maps five dominating dissociation channels of CF42+ as well as one three-body fragmentation channel of CF43+ are identified. The kinetic energy release (KER) distributions for these channels are obtained and compared with the data available in the literature. The Dalitz-like momentum diagram and the Newton diagram are employed to analyze the breakup mechanism in the three-body fragmentation channel. We found that, for CF42+ dissociation into F++CF2++F, F++CF++2F, and F++F++CF2, the concerted breakup is the dominating process. Channel C++F++3F is dominated by the initial charge separation, i.e., CF42+→F++CF++2F→C++F++3F. With the help of the native frame method, we assigned one sequential pathway and two concerted pathways for channel CF43+→F++F++CF2+. The branching ratios of these pathways are determined. The momentum correlation of the fragments and the deduced KER distribution indicate that different excited states of CF43+ with different geometries are responsible for these three pathways. The Coulomb explosion model simulation shows that most of the events in this channel are produced by CF43+ ions that have deformed geometries from the neutral CF4 molecule.